MENINGKATKAN MINAT PEMBELIAN MENGGUNAKAN E-COMMERCE SHOPEE MELALUI IKLAN DAN CITRA MEREK DIMEDIASI KEPERCAYAAN KONSUMEN DI MASA PANDEMI COVID-19 - Yunita Ramadhani Ratnaningsih DS (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to examine the effect of advertising, brand image and consumer trust on online buying interest. This study also aims to examine the effect of advertising and brand image on consumer trust in E-Commerce Shopee. This research is a quantitative research, the sampling method used is non-probability sampling with purposive sampling type. The population in this study were all Shopee users in Bekasi Regency and the sample used was 214 Shopee users aged over 17 years and domiciled in Bekasi Regency. The analysis technique used is Structural Equation Modeling (SEM) with the help of AMOS 23 software. The results of this study indicate that there is a significant influence between brand image on consumer trust, advertising on consumer trust and advertising on buying interest, while brand image on buying interest and trust on buying interest does not have a significant effect.